2013
DOI: 10.1007/s00210-013-0922-8
|View full text |Cite
|
Sign up to set email alerts
|

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes

Abstract: Many studies demonstrate that accumulation of reactive aldehydes plays an important role in cellular oxidative injury and aldehyde dehydrogenase 2 (ALDH2)-mediated detoxification of reactive aldehydes is thought as an endogenous protective mechanism against cell injury. This study was performed to explore whether Alda-1, a newly identified ALDH2 activator, was able to protect brain against ischemia/reperfusion injury through clearance of reactive aldehydes. In a rat model of focal cerebral ischemia/reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 26 publications
4
61
0
5
Order By: Relevance
“…Several phenomena observed during brain ischemia and reperfusion can be attributed to damage to membrane lipids, especially by lipolysis during ischemia and by radical-mediated peroxidation of polyunsaturated fatty acids [31]. Lipid peroxidation is one of the major mechanisms responsible for the cellular damage caused by oxidative stress, and MDA is one of the main end products of lipid peroxidation which is accumulated during ischemia/reperfusion [5]. Hoseinzadeh et al found that safranal significantly reduced the MDA level in the rat hippocampus [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several phenomena observed during brain ischemia and reperfusion can be attributed to damage to membrane lipids, especially by lipolysis during ischemia and by radical-mediated peroxidation of polyunsaturated fatty acids [31]. Lipid peroxidation is one of the major mechanisms responsible for the cellular damage caused by oxidative stress, and MDA is one of the main end products of lipid peroxidation which is accumulated during ischemia/reperfusion [5]. Hoseinzadeh et al found that safranal significantly reduced the MDA level in the rat hippocampus [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the beneficial influence of ALDH2 stimulation in acute ischemia‐reperfusion injury of heart or brain has been attributed to many possible mechanisms, including attenuation of oxidative stress and clearance of reactive aldehydes, 26 improvement of mitochondrial function and decrease of apoptosis, 27 and augmentation 28 or inhibition of autophagy. 29 In our setting, Alda‐1 tended to decrease the content of 4‐HNE protein adducts and nitrotyrosine in atherosclerotic plaques, but such action did not reached statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The method for sample preparation was described previously by Fu et al [5]. For Western blot analysis, samples containing 20-60 μg of total protein were subjected to SDS/PAGE (10 % gel) and the proteins were transferred on to PVDF membranes.…”
Section: Determination Of Glt-1 Protein Expressionmentioning
confidence: 99%